- 4 2/3 : (-1 1/6) = 14/3 : 7/6 = 14/3 · 6/7 = (2·2)/(1·1) = 4
- 7 1/2 : 3 3/4 = - 15/2 : 15/4 = - 15/2 · 4/15 = - 4/2 = - 2
9 1/3 : (-6 2/9) = 28/3 : (-56/9) = 28/3 · (-9/56) = - (1·3)/(1·2) = - 3/2 = - 1 1/2
Пояснения:
(-) : (-) = (+)
(-) : (+) = (-)
(+) : (-) = (-)
- 4 2/3 : (-1 1/6) = 14/3 : 7/6 = 14/3 · 6/7 = (2·2)/(1·1) = 4
- 7 1/2 : 3 3/4 = - 15/2 : 15/4 = - 15/2 · 4/15 = - 4/2 = - 2
9 1/3 : (-6 2/9) = 28/3 : (-56/9) = 28/3 · (-9/56) = - (1·3)/(1·2) = - 3/2 = - 1 1/2
Пояснения:
(-) : (-) = (+)
(-) : (+) = (-)
(+) : (-) = (-)